2018
DOI: 10.3390/ijms19113325
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Labeling Highlights Enhanced Fatty Acid and Lipid Metabolism in Human Acute Myeloid Leukemia

Abstract: Background: In Acute Myeloid Leukemia (AML), a complete response to chemotherapy is usually obtained after conventional chemotherapy but overall patient survival is poor due to highly frequent relapses. As opposed to chronic myeloid leukemia, B lymphoma or multiple myeloma, AML is one of the rare malignant hemopathies the therapy of which has not significantly improved during the past 30 years despite intense research efforts. One promising approach is to determine metabolic dependencies in AML cells. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 68 publications
0
46
0
Order By: Relevance
“…Thus, complimentary secretome findings from other stem cell sources will provide a powerful reference for the identification of similar factors within the NSC secretome. Finally, the advent of techniques such as SILAC will help identify NSC-secreted proteins (Prokhorova et al, 2009) and/or lipids (Stuani et al, 2018) in co-culture.…”
Section: Modulation Of Cellular Responses Nsc-secreted Factors and Immentioning
confidence: 99%
“…Thus, complimentary secretome findings from other stem cell sources will provide a powerful reference for the identification of similar factors within the NSC secretome. Finally, the advent of techniques such as SILAC will help identify NSC-secreted proteins (Prokhorova et al, 2009) and/or lipids (Stuani et al, 2018) in co-culture.…”
Section: Modulation Of Cellular Responses Nsc-secreted Factors and Immentioning
confidence: 99%
“…Experiments on acute myeloid leukemia HL60 line have demonstrated that IDH1 mutation causes an increase in lipid anabolic fluxes [98] and significantly more MUFA and more SFA, albeit not statistically significantly (p = 0.07) [98]. In the same experiment, the level of PUFA in the studied cells did not differ between those with or without the IDH mutation (p = 0.6) [98]. The observed changes were confirmed on the glioma tumor with and without the IDH1 mutation.…”
Section: Effect Of Mutation In Idh1/2 Genes On the Expression Of Desamentioning
confidence: 99%
“…This makes fatty acids robust biomarker candidates. Recent studies have shown that genetic alterations observed in acute myeloid leukemia (AML) patients control lipid dynamics and metabolism [ 39 , 85 ]. Interestingly, patients with AML can be identified by specific lipid signatures in plasma [ 86 ] and bone marrow [ 87 ].…”
Section: Lipids As Biomarkers Of Immune Response To Cancermentioning
confidence: 99%